We're born to learn : using the brain's natural learning process to create today's curriculum - Smilkstein, Rita. (Thousand Oaks, Calif. : Corwin Press, 2011)
'This updated book on the brain's natural learning process offers practical methods for teaching all students to take responsibility for their own success'-- Provided by publisher.
'In this updated edition of the extraordinary book that linked brain research and the classroom, Smilkstein incorporates all-new research on brain-compatible teaching and the implications of the brain's natural learning process for how teachers can design and deliver effective lesson plans and curriculum. The author's unique research with almost 7,000 students and educators reveals how people experience their own natural learning. In this book Smilkstein breaks down the physiological as well as the emotional development of learning into practitioner-friendly terms well-grounded in research, with special emphasis in this revised edition upon the use of technology in schools; strategies to reach gifted students as well as those who are diagnosed with ADD, ADHD, and autism spectrum disorders; and upon the 7 magic words--'see if you can figure this out'--that lie at the heart of curriculum development to engage all learners'-- Provided by publisher.
Machine generated contents note: Foreword by James H. BerryPrefaceAcknowledgmentsAbout the AuthorIntroduction What This Book Is About Why Study the Brain? Experienced Educators and the Research The Learning Paradigm Assumptions Where We Have Been Where We Are Today This BookPART I: Research in the Classroom and in the Brain Lab1. Learning and Teaching Eye-Opening Experiences in the Classroom The Natural Human Learning Process and Brain Research The Breakthrough Classroom The Research-Based Stages, Curriculum, and Lesson Plans 2. How People Learn: The Natural Human Learning Process (NHLP): The Missing Link: The Breakthrough Critical and Creative Thinking by Infants and Children An Example of Children's Critical and Creative Thinking Critical and Creative Thinking in School The Natural Human Learning Process and School The Natural Human Learning Process (NHLP) Research After the Research Is Over Research Reports The Importance of Making Mistakes Where We Go From Here3. How the Brain Learns: The Brain's Natural Learning Process Introducing the Brain Getting to Know the Brain How the Brain Learns Convergence of Ceiling Levels and Neural Networks Pruning Experience and Brain Growth Constructivism How the Brain Thinks and Remembers The Brain's Innate Resources and Rules Children's Brains and Adults' Brains The Brain Grows Holistically with Plasticity Implications for Curriculum Development What About Piaget? The Breakthrough Theory of Learning4. Personal Experience, Individual Differences, and Learning Emotions and the Brain Negative and Positive Self-Image Networks Learning from Experience Learning Styles, Preferences, and Multiple Intelligences Gifted Students Aptitudes Special Needs, Learning Differences, Autism, ADD, and ADHD The Seven Magic Words: See If You Can Figure It Out Tests Beyond Individual Differences A Handout for Students5. The Student's Experience: Metacognition, Motivation, Self-Evaluation, Achievement, and Technology Self Taught Metacognition and Motivation Intrinsic Rewards Removing the Barriers Self-Evaluation and Metacognition Another Metacognitive Experience Achievement Writing Samples Age and Achievement Technology Self TaughtPART II: Theory and Application6. Sequencing of the Curriculum Challenges The Missing Link Two Problems Neuroscience and Education Converging Research The Theory and Guide Putting the Theory into Practice Thinking at Higher Levels Constructing New Knowledge Planning the Sequence of the Units or Topics in a Curriculum Using a Causal Sequence Learning Activities for Units and Topics The First Activity Two Classroom Examples Students and the NHLP Developing a Curriculum Young Students Thinking at a High Level The NHLP in the Classroom7. The Pedagogical Model and Guidelines Transfer Four Effective Instructional Practices NHLP Pedagogical Guidelines Assessment Education Courses or Faculty Development Programs Good NewsPART III: Using the Brain's Natural Learning Process to Create Curriculum8. Brain-Based, Natural Learning Across the Curriculum The Seven Magic Words in Action Safety Respect The Opportunity to Learn Naturally The Critical First Stages The Introduction-to-Poetry Unit Front Loading A Science Learning Activity about the Concept of Buoyancy A Unit for Library Orientation A Unit for Introduction to Safety Procedures A Science Learning Activity about Water A Unit for Learning How to Take Lecture Notes The NHLP Planning Guidelines and Pedagogy9. Curriculum Development for Units, Courses, and Programs Where to Start Curriculum Development Guidelines A Unit on Literal and Inferential Meaning A Unit on an Introduction to Egypt A Unit on an Introduction to Fractions A Basic Grammar Curriculum: A Sequence of Units for a Whole Course A Developmental English Curriculum: Courses in a ProgramReferencesGeneral BibliographyIndex.
Includes bibliographical references and index.
Keywords: Learning; Curriculum planning; Brain research; EDUCATION / Teaching Methods & Materials / General